Cladocopium community divergence in two Acropora coral hosts across multiple spatial scales - Sarah W. Davies; Kelsey N. Moreland; Drew C. Wham; Matt R. Kanke; Mikhail V. Matz (Molecular Ecology, 2020)
Many broadly‐dispersing corals acquire their algal symbionts (Symbiodiniaceae) “horizontally” from their environment upon recruitment. Horizontal transmission could promote coral fitness across diverse environments provided that corals can associate with divergent algae across their range and that these symbionts exhibit reduced dispersal potential. Here we quantified community divergence of Cladocopium algal symbionts in two coral host species ( Acropora hyacinthus, Acropora digitifera ) across two spatial scales (reefs on the same island, and between islands) across the Micronesian archipelago using microsatellites. We find that both hosts associated with a variety of multilocus genotypes (MLG) within two genetically distinct Cladocopium lineages (C40, C21), confirming that Acropora coral hosts associate with a range of Cladocopium symbionts across this region. Both C40 and C21 included multiple asexual lineages bearing identical MLGs, many of which spanned host species, reef sites within islands, and even different islands. Both C40 and C21 exhibited moderate host specialization and divergence across islands. In addition, within every island, algal symbiont communities were significantly clustered by both host species and reef site, highlighting that coral‐associated Cladocopium communities are structured across small spatial scales and within hosts on the same reef. This is in stark contrast to their coral hosts, which never exhibited significant genetic divergence between reefs on the same island. These results support the view that horizontal transmission could improve local fitness for broadly dispersing Acropora coral species.